The road to political democracy : from Plato to the Charter of Fundamental Rights of the European Union - Senelle, Robert, 1918- (Academic and Scientific Publishers, 2012)
How did democracy, a regime of a numerically insignificant minority in Antiquity, evolve to a 21st century self-evidence in (and beyond) the Western world? That is what this book is about. 'The Road to Political Democracy' is two books in one. In the first part it drafts the red line of the growth of democracy, through the enhancement of its four main Aristotelian features: the rule by turn, the rule of law, education and the role of the middle class. What lessons can we learn from that maturation today? In its second part it describes and cites the historical milestones in the evolution of the democratic regime. It covers twenty-five centuries of evolution, starting with Plato's and Aristotle's works in Greek Antiquity to today's question as to whether democracy is a universal value. This book will guide readers through all the pioneering stages through which political democracy has passed.